BOARD GAME AS LEARNING MEDIA FOR TPQ AL HUDA BABADAN BARU UNGARAN - Oktavani, Veni (Jurusan Seni Rupa Fakultas Bahasa dan Seni, 2020)
The design of board games as a learning media for TPQ Al Huda is motivated by the realization of the teacher on the high enthusiasm of students when conducting Friday's agenda which is filled with playing. Realize with that kind of situations, the teacher wants to take advantage of this condition by giving educative games because the needs of students who not just playing but also to have basic knowledge of dinul Islam in order to understand and practice the Quran. The design begins with by analyzing the needs of students, determining the design strategy and the making of element visual appropriate with the characteristics of the age of the target audience. The purpose of making this design is to produce a classic board game as a learning media who could create fun learning situations. Board Game implementation is expected to motivate the students and to teach the basics of dinul Islam with fun way so the students are enjoy the learning proses